Brain cell type-specific cholesterol metabolism and implications for learning and memory. Issue 5 (May 2022) - Li, Dingfeng; Zhang, Juan; Liu, Qiang
Abstract : Cholesterol homeostasis is vital for brain function. Brain cholesterol is locally synthesized, with varying synthesis capacities across different cell types. Moreover, brain cholesterol horizontally transfers across various cell types not only to accommodate distinct cholesterol needs, but also to fulfill regulatory functions in target cells. Cholesterol metabolism within individual cell types is essential for brain functioning, and the role of cholesterol-related communication between different cell types is gaining growing recognition. Cholesterol metabolism dysfunction is tightly associated with brain aging and Alzheimer's disease (AD). Here, we provide an overview of recent studies on cholesterol metabolism within specific cell types and in relation to the interplay between different cell types. We also discuss the implications of these processes for learning and memory, and their relevance to brain aging and AD. Highlights: Brain cholesterol has a long half-life and is able to transfer across various cell types. Cholesterol metabolism in both neurons and glial cells contributes to learning and memory. Astrocytes not only provide metabolic substances to neurons, but can also metabolically suppress neuronal cholesterol synthesis and promote neuronal functions via secreted effector molecules. Microglia regulate cholesterol metabolism and contribute to learning and memory, in part, by promoting cholesterol elimination. Microglial survival is dependent on both the microglial-specific receptor TREM2 and apolipoprotein E (ApoE)-mediated transport of exogenous cholesterol. Oligodendrocytes support neuronal functions via myelination, which heavily relies on de novo cholesterol biosynthesis in oligodendrocytes and the differentiation from oligodendrocyte progenitor cells to myelin-forming oligodendrocytes. Aged brains exhibit reduced cholesterol biosynthesis and decreased myelination, which both contribute to memory decline. Alzheimer disease brains show reduced cholesterol biosynthesis and turnover. ApoE-mediated cholesterol uptake is essential for amyloid-β precursor protein processing and amyloid-β production.